A prospective analysis of clinical efficacy and safety in chronic myeloid leukemia‐chronic phase patients with imatinib resistance or intolerance as evaluated using European LeukemiaNet 2013 criteria. (25th March 2015) - Murai, Kazunori; Akagi, Tomoaki; Shimosegawa, Kenji; Sugawara, Tomohiro; Ishizawa, Kenichi; Ito, Shigeki; Murai, Keiko; Motegi, Mutsuhito; Yokoyama, Hisayuki; Noji, Hideyoshi; Tajima, Katsushi; Kimura, Jun; et al.
Abstract: Background: We conducted a phase II study to evaluate the efficacy and safety of dasatinib in Japanese patients with imatinib‐resistant or imatinib‐intolerant chronic myeloid leukemia (CML). Methods: From 2009 to 2011, 54 CML‐chronic phase (CP) patients with resistance ( n  = 40) or intolerance ( n  = 25) to imatinib were registered to undergo dasatinib treatment. Eleven patients showed both resistance and intolerance to imatinib. Coincidentally, the resistance criteria in this study were the same as a non‐optimal response to tyrosine kinase inhibitors (TKIs) as defined in the European LeukemiaNet (ELN) 2013 recommendations. Results: The overall incidence rate of major molecular response (MMR) at 12 months was 62.3% ( n  = 47). Forty patients with resistance to imatinib who were 'warning' and 'failure' patients based on the ELN 2013 recommendations were assessed; cumulative MMR and MR 4.5 rates were 62.5% ( n  = 39) and 21.0% ( n  = 40), respectively, at 12 months. Twelve patients who showed a BCR‐ABL transcript level >1% on the international scale did not achieve a MMR or discontinued dasatinib treatment because of insufficient effects. With regard to safety issues, grade 3/4 non‐hematologic adverse events (AEs) were infrequent. Conclusions: Patients with non‐optimal responses (who meet ELN 2013 warning and failure criteria) to imatinib should be switched quickly to dasatinib, which is less toxic in CML‐CP patients, to improve their prognoses. A BCR‐ABL1 IS of <1% at 3 months of dasatinib administration is a landmark for good therapeutic outcome.